Mengurangi Pengaruh Noise Baseline Wander pada Sinyal Electrocardiogram(ECG) - Iman Fahruzi (Politeknik Negeri Batam, 2013)
ECG signal is one of the main tools used to make the diagnosis of heart abnormalities and can also be used to determine the steps recovery before a more serious medical treatment. Description and feature extraction just before taking a decision to be the most important in diagnosing patients' heart health. The main steps in the analysis of the ECG signal is to eliminate or reduce the noise from ECG signals using a variety of filtering techniques, detection of cardiac cycle by detecting QRS complex signal, the detection of the main characteristics of the signal to be analyzed and ultimately determine the formula of the characteristic features that have been obtained in the previous section. In this study, the authors will examine the ECG signal by eliminating or reducing noise on the signal ECG wave pattern up and down making it very difficult for the detection and extraction of ECG signals. The current results of testing showed that the ECG signal which initially did not constantly be on the line isolines become ECG signal consistently isolines are on the line so that this condition makes subsequent processing to diagnose cardiac abnormalities in a timely and accurate.